PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN BELAWA KABUPATEN WAJO - Syamsidar, Syamsidar (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine the influence of competence and leadership on the performance of Kecamatan Belawa, Kabupaten Wajo. The data collection technique in this study was a questionnaire. Six villages were the object of this research, with a total of 54 respondents. The data analysis technique used linear regression analysis. Research results show that: 1) competence has a significant positive effect on performance, 2) leadership has a positive and significant impact on performance.